Review of anaesthetic management for cataract surgery in transplant recipients. Issue 1 (January 2020) - Chua, Alfred WY; Chua, Matthew J; Harrisberg, Brian P; Kumar, Chandra M
The prevalence of transplantation is on the increase worldwide. Corneal transplantation is the most common form of human donor transplantation. Transplantation of other organs and bone marrow is established treatment for various end-organ failure and many haematological conditions, respectively. Success and survival of these patients have increased with advances in immunosuppression. Unfortunately, these patients are susceptible to cataract formation as a consequence of immunosuppressive therapy and accelerated progression of several diseases. Topical anaesthesia and regional ophthalmic blocks are ideal for cataract surgery in cooperative adults. General anaesthesia may be required in children, for extremely anxious or claustrophobic adults and for complex surgery such as simultaneous cataract and corneal transplantation. The perioperative anaesthetic management of cataract surgery in a transplant recipient is no different to a standard technique in a healthy adult, but additional challenges are posed by the underlying pathology necessitating transplantation, function of the transplanted organ, physiological and pharmacological problems of allograft denervation, side-effects of immunosuppression, risk of infection and potential for rejection. This narrative review summarises optimal anaesthetic management in transplant recipients undergoing cataract surgery.